Cooperation Management for Practitioners: Managing Social Change with Capacity WORKS - Deutsche Gesellschaft für internati, GIZ GmbH (Springer, 2016)
The Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH possesses over 30 years of experience in managing cooperation worldwide. It has now consolidated its comprehensive expertise by publishing this book. The management model Capacity WORKS is designed for everyone actually involved in cooperation: managers, executives, consultants and advisors in business, governance, public administration and the nonprofit sector. It provides a full introduction to the challenges of successful cooperation management, and supplies practitioners with tried and tested approaches. Five success factors (strategy, cooperation, steering structure, processes, and learning & innovation) delineate the various facets that help focus on the objectives and results of complex cooperation systems. The conceptual framework underlying the success factors is clearly set out, and the success factors are supplemented by an extensive toolbox to support practitioners working in these five areas. At the same time the manual gives readers a broad insight into the world of cooperation management for sustainable development. It includes numerous practical examples, proven contexts of application and glimpses into the work of international cooperation.